Mission San Jose - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the exterior to Mission San Jose, including the entrance to the mission's museum. The sign above the entrance steps reads "Mission San Jose de Guadalupe. Founded June 11, 1797."